Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Studies on melt processable biocomposites of polylactic acid - Joseph, Seena; Deenadayalan, E.; Mahanwar, Prakash A. (Journal of Polymers and the Environment, 2015)
Melt processable microcrystalline cellulose (MCC)/poly(lactic acid) (PLA) composites were successfully prepared by twin-screw extrusion. Several characterization techniques were used to investigate the effect of MCC on rheological behavior, morphology, crystallization and melting behavior of the PLA and structure-property correlation of the MCC/PLA composites has been established. Rheological measurements showed that the addition of MCC has a dramatic influence on the low frequency relaxations of PLA chains and above 5 % of MCC, it forms percolated network structure. Differential scanning calorimeter analysis showed that MCC acted as nucleating agent enhancing crystallization below the percolation concentration. Properties of MCC/PLA composites have been compared with that of talc and CaCO3 filled composites. Talc is found to be more effective in crystallizing PLA than MCC and CaCO3. MCC/PLA composites are found be melt processable like that of talc and CaCO3 filled PLA composites.
Keywords: Biopolymers; composites; Rheological properties; Structure-property relationship